Design of The BK Service Program to Increase The Emotional Maturity of Class X Students at SMA Negeri 9 Sijunjung - Sarah Awalia Reka; Fuaddillah Putra; Wira Solina (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This research is motivated by the existence of students who have difficulty managing emotions. This can be seen from various behaviors such as irritability, impulsivity in making decisions, difficulty controlling oneself when facing conflicts, and tending to respond to stressful situations in a non-adaptive way. Based on an interview with a BK teacher at SMAN 9 Sijunjung in January 2025, there are problems in students such as students who are not able to respect others in their opinions and attitudes, are not able to respond well to others and there are still those who are involved in conflicts with each other, there are students who are not able to be patient in their daily behavior, especially in the school environment. This study aims to find out: 1) BK teachers have not provided emotional maturity services for students at SMA Negeri 9 Sijunjung. 2) designing a BK service program to increase the emotional maturity of SMA Negeri 9 Sijunjung students. This type of research is descriptive quantitative with a correlational approach. The population of this study is 140 people. The sampling technique used Simple Random Sampling with a sample of 103 people. The instrument used in this study is a questionnaire. The data analysis technique in this study uses a descriptive analysis test. The results of this study are about revealing the emotional maturity of students who are in the high category and based on the results of this research it is recommended for BK teachers to be able to provide services and materials in order to increase emotional maturity with service topics, namely: accepting yourself, controlling yourself before acting, being able to control emotions, thinking objectively and responsibly.